Families and Child Health - McHale, Susan M.; Booth, Alan; Landale, Nancy S. (National Symposium on Family Issues, 2013)
An adult's health is determined not only by stress levels, food choices, and recreational habits. Science is paying increased attention to the roles of prenatal, perinatal, and early childhood conditions in shaping health and well-being across the lifespan. Families and Child Health brings clarity to this complex and multifaceted topic. This comprehensive volume presents analyses of the interactions between the "nature" and "nurture" components of the equation, providing current findings on in utero nutrition and development and examining the roles of social determinants and family discord in the creation of health disparities. Contributors emphasize opportunities for prevention and intervention and make the case for interdisciplinary collaboration. Among the topics covered in depth are: Early developmental origins of chronic disease. Lifecourse exposures and social disparities in child health. The science of designing, implementing, and evaluating programs and policies for child health. Effects of early psychosocial deprivation on children's cognitive and social development. The family-friendly workplace and its impact on child and family health. Integrating perspectives on children's health. Families and Child Health is bedrock reading for researchers, professors, and graduate students in disparate fields such as policy analysis, human development, family studies, sociology, social welfare, family demography, public health, health science, clinical psychology, social psychology, behavioral medicine, and public policy. Policymakers will also find it of considerable importance.